Resource Allocation Achieving High System Throughput with QoS Support in OFDMA-Based System - Lee, Tsern-Huei; Huang, Yu-Wen (My University, 2012)
In this paper, we present a resource allocation algorithm for OFDMA-based systems which handles both real-time and non-real-time traffic. For real-time traffic, the QoS requirements are specified with delay bound and loss probability. The resource allocation problem is formulated as one which maximizes system throughput subject to the constraint that the bandwidth allocated to a flow is no less than its minimum requested bandwidth, a value computed based on loss probability requirement and running loss probability. A user-level proportional-loss scheduler is adopted to determine the resource share for flows attached to the same subscriber station (SS). In case the available resource is not sufficient to provide every flow its minimum requested bandwidth, we maximize the amount of real-time traffic transmitted subject to the constraint that the bandwidth allocated to an SS is no greater than the sum of minimum requested bandwidths of all flows attached to it. Moreover, a pre-processor is added to maximize the number of real-time flows attached to each SS that meet their QoS requirements. We show that, in any frame, the proposed proportional-loss scheduler guarantees QoS if there is any scheduler which guarantees QoS. Simulation results reveal that our proposed algorithm performs better than previous works.
Keywords: OFDMA; QoS; delay bound; loss probability; proportional-loss